Clinical Utility of Bioelectrical Impedance Analysis Parameters for Evaluating Patients with Lower Limb Lymphedema after Lymphovenous Anastomosis - Son, Woo Chul; Kwon, Jin Geun; Hong, Joon Pio; Park, Chang Sik; Kim, Sang Ah; Do, Jung Hwa; Cheon, Hwayeong; Gelvosa, Ma Nessa; Suh, Hyun Suk; Jeon, Jae Yong (Journal of Reconstructive Microsurgery, 2022)
Background In lymphedema, lymphatic fluid accumulates in the interstitial space, and localized swelling appears. Lymphovenous anastomosis (LVA) is the most widely used surgery to rebuild a damaged lymphatic system; however, assessing outcome of LVA involves performing volume measurements, which provides limited information on body composition changes. Therefore, we analyzed the bioelectrical impedance analysis (BIA) parameters that can reflect the status of lymphedema patients who underwent LVA.Methods We retrospectively reviewed records of 42 patients with unilateral lower extremity lymphedema who had LVA. We measured the perioperative BIA parameters such as extracellular water (ECW) ratio and volume as defined by the percentage of excess volume (PEV). We evaluated the relationship between the amount of change in PEV and in BIA parameters before and after surgery. We confirmed the correlation between ΔPEV and BIA parameters using Spearman's correlation.Results Most patients included had secondary lymphedema due to cancer. Average age was 51.76 years and average body mass index was 23.27. PEV and all BIA parameters after surgery showed a significant difference (p < 0.01) compared with preoperative measurements. The ECW ratio aff/unaff showed the strongest correlation with PEV with a correlation coefficient of 0.473 (p < 0.01).Conclusion Our findings suggest that BIA parameters, especially ECW ratio aff/unaff could reflect the status of patients with lower limb lymphedema after LVA. Appropriate use of BIA parameters may be useful in the postoperative surveillance of patients.
Keywords: lymphedema; lymphovenous anastomosis; bioelectrical impedance analysis